ROLE OF FIBRINOLYTIC ACTIVITY OF BLOOD IN PATHOGENESIS OF NON-ALCOHOLIC FATTY LIVER DISEASE AND CHRONIC KIDNEY DISEASE (ORIGINAL RESEARCH) - A. A. Antoniv (Eastern Ukrainian Medical Journal, 2019)
The aim of the research − to find out of changes fibrinolytic activity of blood in patients with non-alcoholic fatty liver on the background of obesity, depending on the presence of comorbid chronic kidney disease. Material and methods of research: 444 patients were examined: 84 of them were with NAFLD and class I obesity (group 1), which contained 2 subgroups: 32 patients with non-alcoholic steatosis (NAS) and 52 patients with non-alcoholic steatohepatitis (NASH); 270 patients with NAFLD with comorbid class I obesity and CKD І–ІІІ stage (group 2), including 110 patients with NAS and 160 patients with NASH. The control group consisted of 90 patients with CKD of І–ІІІ stage with normal body weight (group 3). To determine the dependence of the NAFLD course on the form and stage of the CKD, the group of patients was randomized according to age, sex, degree of obesity, and activity of NASH. Research results. The study of fibrinolytic activity of blood showed that total fibrinolytic activity (TFA) of blood plasma in patients of all groups was significantly lower than the control indexes: in patients with NAS – by 7.1%, patients with NAS with CKD – by 14.9%, patients with NASH – by 17.2%, patients with NASH with CKD – by 18.9%, patients with CKD – by 10.6% (p <0.05) with the presence of a probable intergroup difference between groups with comorbidity and isolated course of CKD (p <0.05). The suppression of TFA occurred through the decrease of EF: in patients with NAS the index is significantly lower than that in the controls by 1.2 times, in patients with NAS with CKD – by 1.4 times, in patients with NASH – by 1.7 times, in the group of patients with NASH and CKD – by 1.9 times, while in the group of patients with CKD, the suppression of EF was registered – 1.3 times (p <0.05). At the same time, the NEF in patients of all groups increased in comparison with the AHP group: in patients with NAS – by 1.2 times, in patients with NAS with CKD – by 1.3 times, in patients with NASH – by 1.4 times, in the group of patients with NASH with CKD – 1.5 times, while in the group of patients with CKD the activation of NEF was registered 1.2 times (p <0.05), with the presence of a probable difference between the groups with comorbidity and isolated course of CKD (p <0.05). Conclusion. Analysis of hemostasis and fibrinolysis indices in examined patients with NASH, depending on the stage of CKD showed that with the growth of the CKD stage, the activity of the cohort increases, with the exception of the fibrinogen content (most likely due to coagulopathy consumption), the activity of the anti-coagulants decreases, the total and enzymatic activity of fibrinolysis is reduced, and non-enzymatic compensator increases. Thus, metabolic intoxication, oxidative stress, which accompany the flow of NAFLD with obesity and CKD, promote the activation of the kallikrein-kinin system, the formation of plasma and thrombin, with subsequent disturbance of equilibrium between them, the development of stasis, slag phenomenon, the formation of platelet and erythrocyte aggregates in blood circulation system. The consequence of significant activation of hemocoagulation against the suppression of total fibrinolytic activity (TFA) is the local clotting of blood in the arteries.